Institutional Arbitration: India’s Attempt to Transpire as an International Hub of Arbitration in Southeast Asia - Sh. Pachahara (BRICS Law Journal)
International arbitration has flourished as a private adjudicatory forum and is consistently evolving because of its versatile nature, assimilating the needs of modern arbitration users. Arbitration institutes have bent over backward for the development of international arbitration. All jurisdictions, through sporadic amendments, upgrade their curial law in alignment with the current global arbitration norms. The leading jurisdictions of Southeast Asia, specifically Singapore, Malaysia, and Hong Kong, through timely updates in their curial law and atonement of their premier arbitration institute’s policies incorporating the recent trends, continue to grow and rival each other as regional players in international arbitration. Keeping in mind India’s position in the global market, it is about time that India reserves its name among the leading arbitration hubs in Southeast Asia. Upon consideration of the trifecta of the curial law, the role of the premier arbitral institution, and the deference of the judiciary of a leading arbitration hub, the author through critical analysis, coherent reasoning, and statistical interpretation of data attempts to unveil the following questions raised. Firstly, whether India’s endeavour to strengthen and reinforce institutional arbitration in India vide the Amendment Act, 2019 would derive the desired result. Secondly, whether India’s attempt to become an international hub of arbitration that could rival Singapore, Hong Kong, and Malaysian arbitration institutes would be successful. Consequently, India’s attempt to march alongside the leading arbitral forces in Southeast Asia is like a lucid dream having the potential of manifestation.